Dampak Pengawasan Terhadap Produktivitas Kerja Karyawan PT. Surya Perdana Agung Pekanbaru - lamin, lamin (Sekolah Tinggi Ilmu Ekonomi Riau, 2024)
This research aims to examine the influence of supervision on employee work productivity at PT. Surya Perdana Agung Pekanbaru. Data was collected through questionnaires distributed to 33 respondents. The quantitative analysis encompassed validity and reliability tests, classical assumption tests, hypothesis testing through t-test, and coefficient of determination (R2) analysis. The data analysis technique employed was simple regression analysis, which served to validate the research hypothesis. The hypothesis testing through t-test yielded a t-count of 2.689, while the t-table value was 2.036. Therefore, the research hypothesis result showed t-count 2.689 > t-table 2.036, indicating that supervision has a significant effect on employee work productivity. The relationship between supervision and productivity was positive, as evidenced by the regression coefficient (b) of 0.620, meaning that each unit increase in supervision would increase employee work productivity by 0.620 units. The R Square value of 0.189 indicates that the contribution of supervision to employee work productivity at PT. Surya Perdana Agung Pekanbaru is 18.90%.